Biogeography of New World Monkeys - Heads, Michael (Molecular Panbiogeography of the Tropics, 2011)
Detailed information on the molecular phylogeny of New World monkeys (Opazo et al., 2006; Osterholz et al., 2009) and on their distribution and ecology (IUCN, 2009) is now available, and so the group is an excellent subject for biogeographic and evolutionary study. Researchers now agree on many descriptive aspects of the phylogeny and distributions, although the interpretation of the data remains controversial. As yet, there is little agreement on how, when, or where the different primate clades evolved in America or even how primates came to be there in the first place. Most previous work has suggested that primates colonized